Agriculture in South Asia and its implications on downstream health and sustainability: a review - Atapattu, Sithara S.; Kodituwakku, Dekshika Charmini (2009)
Agriculture, a century old practice, has rarely been questioned as it is a necessity for feeding the world's population. With the increase in food requirement, the sustainability of upland agriculture has posed threats to downstream and coastal areas of river basins. In South Asia, the coastal population depends on the lower part of the river basin for their livelihood such as agriculture and aquaculture. There have been numerous occasions where downstream areas have suffered as a consequence of ad hoc agricultural development activities upstream. Problems encountered in the downstream coastal areas include river desiccation, groundwater depletion, water pollution and sedimentation, salinization and salt water intrusion, soil erosion and nutrient depletion, and dynamic changes in the coastal wetland systems. The objective of this paper is to evaluate current agricultural practices, existing problems, and their implications downstream. This would facilitate the adoption of the river basin approach in managing water resources focusing on the South Asian region.